2014
DOI: 10.1007/s13762-014-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of water repellency in the treatment of contaminated muds using the chemical–biological stabilization process

Abstract: The soil-water relationship was used to evaluate the efficacy of a novel remediation technology, the chemical-biological stabilization process, which focuses principally on soil fertility restoration in agricultural sites. This process was evaluated for the treatment of 150 m 3 of bentonitic drilling muds from a closed sulfur mine which contained 70 % fines (\0.05 mm), and which had been contaminated with very weathered hydrocarbons, containing 31 % asphaltenes. This material was monitored for two and a half y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This may maintain the in situ water content above the critical threshold at which water repellency becomes manifest. Similarly, the increase in field capacity was correlated with a reduction in hydrophobicity in soil which have been recovered by phytoremediation techniques (Guzmán and Adams 2014;Sublette et al 2010). In addition to the type and amount of SOM being correlated with soil hydrophobicity, texture has also been implicated.…”
Section: Model For Estimating Wdpt From°api and Oil Concentrationmentioning
confidence: 94%
See 2 more Smart Citations
“…This may maintain the in situ water content above the critical threshold at which water repellency becomes manifest. Similarly, the increase in field capacity was correlated with a reduction in hydrophobicity in soil which have been recovered by phytoremediation techniques (Guzmán and Adams 2014;Sublette et al 2010). In addition to the type and amount of SOM being correlated with soil hydrophobicity, texture has also been implicated.…”
Section: Model For Estimating Wdpt From°api and Oil Concentrationmentioning
confidence: 94%
“…Other authors have also observed this discrepancy between water repellency as measured in the laboratory and actual conditions in the field (Adams et al 2008a;Guzmán and Adams 2014). For 2 years, Guzmán and Adams (2014) monitored the remediation of very clayey, hydrocarbon-contaminated sediments that had been treated using a chemical-biological stabilization technology.…”
Section: Critical Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field, even during the driest part of the year, there may still be some moisture in the soil, which could mitigate water repellency. To determine the CMC at which water repellency is manifested, direct measurement of penetration times of deionized water was made to determine CMC for absorption at \5 and \60 s (nonrepellent to slightly repellent range, according to Dekker and Jungerius 1990), as per Guzmán-Osorio and Adams (2015). -112-1995-SCFI (SECOFI 1996, and Adams et al (2014).…”
Section: Ismc Cmc and Water Repellency Analysesmentioning
confidence: 99%
“…Only a few studies focusing soil WR have been carried out in Mexico. Some of these studies deal with hydrocarbon contaminated soils in the southern Gulf of Mexico region (Adams et al, ; Guzmán‐Osorio and Adams, ). Jordán et al .…”
Section: Introductionmentioning
confidence: 99%